1989
DOI: 10.1128/jcm.27.9.2091-2095.1989
|View full text |Cite
|
Sign up to set email alerts
|

Enterococci highly resistant to penicillin and ampicillin: an emerging clinical problem?

Abstract: Sixteen clinical isolates of ampicillin-resistant enterococci (ARE) were recovered from the microbiology laboratory of a 450-bed rehabilitation medical center from January 1981 to September 1987. These isolates were detected when a disk diffusion test using 10 ,ug of ampicillin on a blood agar plate revealed no zones of inhibition. Tube macrodilution tests yielded an MIC of .16 ,ig of ampicillin per ml. None of the isolates were penicillinase producers by the chromogenic cephalosporin disk test. Ten isolates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…Our patients had been hospitalized for a long time prior to ARE‐infection, had high consumption of antibiotics and a high proportion of the patients had severe underlying diseases. These findings are in accordance with those in other outbreaks[5–14,43]. Many cases of multiple‐drug‐resistant enterococcal infections have been described in debilitated patients with prolonged hospital stay[19–45] who have received multidrug regimens or antimicrobial agents for a long time[15–46].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our patients had been hospitalized for a long time prior to ARE‐infection, had high consumption of antibiotics and a high proportion of the patients had severe underlying diseases. These findings are in accordance with those in other outbreaks[5–14,43]. Many cases of multiple‐drug‐resistant enterococcal infections have been described in debilitated patients with prolonged hospital stay[19–45] who have received multidrug regimens or antimicrobial agents for a long time[15–46].…”
Section: Discussionsupporting
confidence: 88%
“…Several factors have also been suggested as modifiers of the outcome of enterococcal infection, among them ampicillin resistance[5–24]. None of the fatal cases in this study was found in patients without underlying severe and life‐threatening diseases.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Ampicillin resistance among enterococcal isolates was reported to be rare in a survey of 382 isolates in 1969 (35). Since then there have been several reports of a growing clinical problem with ARE (2,3,5,12,30,33). Our study confirms this and illustrates the importance of ARE as nosocomial pathogens.…”
Section: Discussionsupporting
confidence: 85%
“…High-level resistance to aminoglycosides which results in a lack of bactericidal synergism when combined with cell wallactive agents is now frequently seen worldwide (27,31). Ampicillin-resistant enterococci (ARE) are increasingly common in some centers (2,30,33), and more recently, vancomycin-resistant enterococci have been isolated with greater frequency in the United States and Europe (7,10,15,19). It has been reported that the prevalence of vancomycin-resistant enterococci in hospital intensive care units in the United States increased from 0.8% of enterococcal strains in 1989 to an alarming 13.3% by 1993 (9).…”
mentioning
confidence: 99%